2021
DOI: 10.1126/science.abe5146
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Foxp3 by T follicular helper cells in end-stage germinal centers

Abstract: Germinal centers (GCs) are the site of immunoglobulin somatic hypermutation and affinity maturation, processes essential to an effective antibody response. The formation of GCs has been studied in detail, but less is known about what leads to their regression and eventual termination, factors that ultimately limit the extent to which antibodies mature within a single reaction. We show that contraction of immunization-induced GCs is immediately preceded by an acute surge in GC-resident Foxp3+ T cells, attribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 65 publications
1
69
2
Order By: Relevance
“…This suggests that Foxp3 - cells acquired Foxp3 expression after tamoxifen has been cleared, thus giving rise to a Tfr-like population that has escaped ICOS ablation. These findings fit with a recent report showing that Tfh cells can acquire Foxp3 expression at the end-stage of GC reactions 24 . We will henceforth use the term “Tfh-like Tfr” to refer to this population.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This suggests that Foxp3 - cells acquired Foxp3 expression after tamoxifen has been cleared, thus giving rise to a Tfr-like population that has escaped ICOS ablation. These findings fit with a recent report showing that Tfh cells can acquire Foxp3 expression at the end-stage of GC reactions 24 . We will henceforth use the term “Tfh-like Tfr” to refer to this population.…”
Section: Resultssupporting
confidence: 93%
“…The fact that a portion of mature Tfh cells can acquire Foxp3 expression has been recently confirmed by Jacobsen et al . 24 . However, the authors observed this population arising in end-stage germinal centers up to 20 days post-immunization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that the trends were not a consequence of the GC collapse brought about by decaying antigen levels. The trends remained even without GC collapse or when the collapse was due to alternative mechanisms such as restricted T fh cell help ( 57 ) ( Supplementary Figure 9 ). That GCs following COVID-19 vaccination can persist over extended durations ( 24 , 58 ) suggests that GC shrinkage may be slow in vivo .…”
Section: Resultsmentioning
confidence: 97%
“…In contrast, suppressive CD4 + FOXP3+ T regulatory (T reg ) cells, called T follicular regulatory (T FR ) cells, limit the function and output of GC reaction ( Chung et al, 2011 ; Wollenberg et al, 2011 ). While T FR cells dominate the early-GC ( Wing et al, 2017 ), a distinct T reg population prevails in the late-GC ( Jacobsen et al, 2021 ). These recently described cells seem to arise from T FH cells, however it remains unclear what triggers their acquisition of regulatory properties ( Jacobsen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%